Modeling low-level clouds over the Okhotsk Sea in summer: cloud formation and its effects on the Okhotsk high - Koseki, Shunya. (2013)
In summer the Okhotsk Sea is often covered by low-level clouds, which occasionally co-occur with the Okhotsk high. We investigate the formation of low-level clouds and their effects on the Okhotsk high in July using reanalysis, satellite data, and a regional climate model. Statistical analysis suggests that the amount of low-level clouds over the Okhotsk Sea has a positive relationship with the strength of the Okhotsk high; however, the formation processes of the Okhotsk high and low-level clouds are not dependent on each other. A simulation focusing on July 2003, when the Okhotsk high was the strongest in the past decade, showed low-level cloud formation and resulting strong cooling over most of the Okhotsk Sea, which can be attributed to longwave radiation. Sensitivity experiments with reduced cloud amounts reveal that this radiative flux results in the cooling of the cloud top boundary layer (CBL), thereby reinforcing the Okhotsk high within the CBL. Trajectory analyses show that unsaturated air reaches saturation mainly because of the downward sensible heat flux. After cloud formation, radiative cooling causes an upward sensible heat flux below the clouds. Such cooling and heating roughly balance with the cooling due to evaporation of drizzle and cloud water and the heating due to condensation. Eventually, the CBL achieves a low-temperature steady state over the Okhotsk Sea. Although the latent heat flux is positive over the Okhotsk Sea irrespective of the presence or absence of low-level clouds, associated moisture flux is insignificant for achieving saturation. This positive latent heat flux is enhanced under cloudy conditions and compensates for the loss of water vapor due to condensation.